Women in British Caribbean society and the Victorian gender ideology in the post- Emancipation century - Blommestein, Muriel (Department of History, The University of the West Indies, St. Augustine Campus,Trinidad and Tobago, 2011)
The status guided Victorian gender ideology, based on the patriarchal rights of males, was a well established concept in nineteenth century Caribbean societies. It survived as an entrenched Eurocentric paternalism that was accommodated by other patriarchies. It promised respectability through Christian monogamous marriage and middle class wealth, and this solidified its early Christian/capitalist base. In the post-emancipation century, Caribbean women were challenged by this Euro-serving ideology that reflected a ‘gilded’, metropolitan culture. While‘marginalised’ subaltern women grappled with emotional and physical survival in this period, Creole elite women were no less badgered by the rigidity of existing cultural norms from slave society. This discussion looks at the origins and influences of this tenacious ideology on the lifestyles of women in the colonial British Caribbean. Clearly, the ideology maintained ‘clout’ in British Caribbean societies, even when articulated at such an illiberal moment in the history of the region.
Keywords: Women -- History -- West Indies,British.; Gender identity -- History -- West Indies, British.